Dampak Sosial dan Ekonomi dari insiden-insiden Keamanan Informasi Studi kasus KPU Provinsi Jambi - Ahmad Affan; Fahmi Hidayat; Gilang Ramadhan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Information security incidents within government institutions have become a critical issue due to their potential impact on public trust and socio-economic stability. This study examines the social and economic impacts of information security incidents at the General Election Commission (KPU) of Jambi Province. The research aims to identify the types of security incidents that occurred, analyze their social and economic consequences, and evaluate mitigation efforts implemented by the institution. This study employs a qualitative case study approach, using data collection techniques including document analysis, media reports, and interviews with relevant stakeholders. The findings indicate that information security incidents significantly affect public trust in electoral institutions, increase public anxiety regarding personal data protection, and generate additional economic costs related to system recovery, security enhancement, and administrative delays. Furthermore, the incidents also indirectly affect voter participation and institutional reputation. The study highlights the importance of strengthening information security governance, improving human resource awareness, and implementing comprehensive risk management strategies. The results of this research are expected to contribute to the development of more resilient information security policies in public sector institutions, particularly in electoral management bodies.